Lifesaving decompressive craniectomy for high intracranial pressure attributed to deep-seated meningioma: Emergency management - Haq, Irwan; Niantiarno, Fajar; Arifianto, Muhammad; Nagm, Alhusain; Susilo, Rahadian; Wahyuhadi, Joni; Goto, Takeo; Ohata, Kenji (Asian Journal of Neurosurgery, 2021)
Objects: As the most common intracranial extra-axial tumor among adults who tend to grow slowly with minimal clinical manifestation, the patients with meningioma could also fall in neurological emergency and even life-threatening status due to high intracranial pressure (ICP). In those circumstances, decompressive craniectomy (DC) without definitive tumor resection might offer an alternative treatment to alleviate acute increasing of ICP. The current report defines criteria for the indications of lifesaving DC for high ICP caused by deep-seated meningioma as an emergency management. Patients and Methods: This study collected the candidates from 2012 to 2018 at Dr. Soetomo General Hospital, Surabaya, Indonesia. The sample included all meningioma patients who came to our ER who fulfilled the clinical (life-threatening decrease in Glasgow Coma Scale [GCS]) and radiography (deep-seated meningioma, midline shift in brain computed tomography [CT] >0.5 cm, and diameter of tumor >4 cm or tumor that involves the temporal lobe) criteria for emergency DC as a lifesaving procedure. GCS, midline shift, tumor diameter, and volume based on CT were evaluated before DC. Immediate postoperative GCS, time to tumor resection, and Glasgow Outcome Scale (GOS) were also assessed postoperation. Results: The study enrolled 14 patients, with an average preoperative GCS being 9.29 ± 1.38, whereas the mean midline shift was 15.84 ± 7.02 mm. The average of number of tumor's diameter and volume was 5.59 ± 1.44 cm and 66.76 ± 49.44 cc, respectively. Postoperation, the average time interval between DC and definitive tumor resection surgery was 5.07 ± 3.12 days. The average immediate of GCS postoperation was 10.07 ± 2.97, and the average GOS was 3.93 ± 1.27. Conclusion: When emergency tumor resection could not be performed due to some limitation, as in developing countries, DC without tumor resection possibly offers lifesaving procedure in order to alleviate acute increasing ICP before the definitive surgical procedure is carried out. DC might also prevent a higher risk of morbidity and postoperative complications caused by peritumoral brain edema.
Keywords: Decompressive craniectomy; lifesaving; meningioma; skull base surgery